Multicolor and 3D Holography Generated by Inverse‐Designed Single‐Cell Metasurfaces. Issue 17 (18th March 2023) - So, Sunae; Kim, Joohoon; Badloe, Trevon; Lee, Chihun; Yang, Younghwan; Kang, Hyunjung; Rho, Junsuk
Abstract : Metasurface‐generated holography has emerged as a promising route for fully reproducing vivid scenes by manipulating the optical properties of light using ultra‐compact devices. However, achieving multiple holographic images using a single metasurface is still difficult due to the capacity limit of a single meta‐atom. In this work, an inverse design method based on gradient‐descent optimization is presented to encode multiple pieces of holographic information into a single metasurface. The proposed method allows the inverse design of single‐cell metasurfaces without the need for complex meta‐atom design strategies, facilitating high‐throughput fabrication using broadband low‐loss materials. By exploiting the proposed design method, both multiplane red‐green‐blue (RGB) color and three‐dimensional (3D) holograms are designed and experimentally demonstrated. Multiplane RGB color holograms with nine distinct holograms are achieved, which demonstrate the state‐of‐the‐art data capacity of a phase‐only metasurface. The first experimental demonstration of metasurface‐generated 3D holograms with completely independent and distinct images in each plane is also presented. The current research findings provide a viable route for practical metasurface‐generated holography by demonstrating the high‐density holography produced by a single metasurface. It is expected to ultimately lead to optical storage, display, and full‐color imaging applications. Abstract : S. So, J. Kim, T. Badloe, C. Lee, Y. Yang, H. Kang, J. Rho Metasurface‐generated multicolor and three‐dimensional holography is demonstrated using single‐cell metasurfaces. By using an inverse design based on gradient‐descent optimization, multiple pieces of holographic information are encoded into a single‐cell metasurface. The designed single‐cell metasurfaces demonstrate the state‐of‐the‐art data capacity of a phase‐only metasurface. The inverse‐designed single‐cell metasurfaces are experimentally realized using a high‐throughput nanoimprint lithography fabrication method.